PENGARUH GOOD GOVERNMENT, PENGENDALIAN INTERN, DAN BUDAYA TRI HITA KARANA PADA KINERJA ORGANISASI PERANGKAT DAERAH DI KABUPATEN KARANGASEM - Wirawati, Ni Gusti Putu; Badera, I Dewa Nyoman; Putri, I. G. A. M. Asri Dwija (Buletin Studi Ekonomi, 2020)
This research aims to examine the effect of good government governance, internal control, Tri Hita Karana culture on the Performance of Regional Apparatus Organization. This research was conducted in Karangasem Regency with 96 respondents from the regional apparatus. Determination of the sample using non-probability sampling with saturation sampling technique. Data collection methods were carried out using questionnaires and data analysis technique using multiple linear regression analysis. The results of this research indicate that the variables of government governance, internal control, Tri Hita Karana culture have a positive effect on the Performance of Regional Apparatus Organization in Karangasem Regency.